RELATIONSHIPS BETWEEN COMBITIES AND DEATHS DUE TO COVID-19 IN SANTA CATARINA - Rodrigues, Alexsandro; Martins Silva, Lisiane; Aparecida Leopoldino Cardoso, Analieze (Health and Society, 2023)
This article is the result of a project developed in the Completion Work discipline of the Degree in Biological Sciences at the Center for Distance Education at the State University of Santa Catarina - UDESC. The main objective was to relate comorbidities with deaths resulting from COVID-19, seeking to corroborate data from scientific articles and information provided by the Department of Health of Santa Catarina (SES/SC) on deaths of patients from the disease and those with comorbidities, reaching data that show that in fact there were more deaths from COVID-19 in people who had some type of comorbidity compared to patients who only acquired the disease. Based on the research, it is concluded that having one or more comorbidities has corroborated a considerable record with the increase in the number of deaths among those affected by the COVID-19 disease.